2013
DOI: 10.1093/ndt/gfs530
|View full text |Cite
|
Sign up to set email alerts
|

Online haemodiafiltration: definition, dose quantification and safety revisited

Abstract: The general objective assigned to the EUropean DIALlysis (EUDIAL) Working Group by the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) was to enhance the quality of dialysis therapies in Europe in the broadest possible sense. Given the increasing interest in convective therapies, the Working Group has started by focusing on haemodiafiltration (HDF) therapies. Several reports suggest that those therapies potentially improve the outcomes for end-stage renal disease patients. Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
256
0
30

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(289 citation statements)
references
References 29 publications
3
256
0
30
Order By: Relevance
“…Today, sterile substitution fluid is prepared online, thus enabling production of large volumes of substitution fluid at an acceptable cost in everyday clinical practice. 2 Increased interest in HDF was triggered by analysis of European Dialysis Outcomes and Practice Patterns Study (DOPPS) data. 3 This retrospective study suggests that use of HDF confers a survival benefit compared with HD.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Today, sterile substitution fluid is prepared online, thus enabling production of large volumes of substitution fluid at an acceptable cost in everyday clinical practice. 2 Increased interest in HDF was triggered by analysis of European Dialysis Outcomes and Practice Patterns Study (DOPPS) data. 3 This retrospective study suggests that use of HDF confers a survival benefit compared with HD.…”
mentioning
confidence: 99%
“…This working group has produced one paper summarizing definitions, dose quantification, and safety; a second paper on clinical evidence will be released shortly. 2 Several important aspects of HDF have not been addressed so far. The above-mentioned randomized trials used the traditional schedule of three treatments per week, thus addressing the question of whether HDF can provide a better outcome in that logistic and organizational infrastructure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…40 Three RCTs have compared survival and cardiovascular events in patients allocated to HDF versus conventional hemodialysis. One study observed better outcomes with HDF, 41 whereas the other two studies found no difference.…”
Section: Nontraditional Cardiac Risk Factors and Cardiovascular Mortamentioning
confidence: 99%